Open system sulphate reduction in a diagenetic environment – Isotopic analysis of barite (δ34S and δ18O) and pyrite (δ34S) from the Tom and Jason Late Devonian Zn–Pb–Ba deposits, Selwyn Basin, Canada. (1st May 2016) - Magnall, J.M.; Gleeson, S.A.; Stern, R.A.; Newton, R.J.; Poulton, S.W.; Paradis, S.
Abstract: Highly positive δ 34 S values in sulphide minerals are a common feature of shale hosted massive sulphide deposits (SHMS). Often this is attributed to near quantitative consumption of seawater sulphate, and for Paleozoic strata of the Selwyn Basin (Canada), this is thought to occur during bacterial sulphate reduction (BSR) in a restricted, euxinic water column. In this study, we focus on drill-core samples of sulphide and barite mineralisation from two Late Devonian SHMS deposits (Tom and Jason, Macmillan Pass, Selwyn Basin), to evaluate this euxinic basin model. The paragenetic relationship between barite, pyrite and hydrothermal base metal sulphides has been determined using transmitted and reflected light microscopy, and backscatter electron imaging. This petrographic framework provides the context for in-situ isotopic microanalysis (secondary ion mass spectrometry; SIMS) of barite and pyrite. These data are supplemented by analyses of δ 34 S values for bulk rock pyrite ( n = 37) from drill-core samples of un-mineralised (barren), siliceous mudstone, to provide a means by which to evaluate the mass balance of sulphur in the host rock. Three generations of barite have been identified, all of which pre-date hydrothermal input. Isotopically, the three generations of barite have overlapping distributions of δ 34 S and δ 18 O values (+22.5‰ to +33.0‰ and +16.4‰ to +18.3‰, respectively) and are consistent with an origin from modified Late Devonian seawater. Radiolarian tests, enriched in barium, are abundant within the siliceous mudstones, providing evidence that primary barium enrichment was associated with biologic activity. We therefore propose that barite formed following remobilisation of productivity-derived barium within the sediment, and precipitated within diagenetic pore fluids close to the sediment water interface. Two generations of pyrite are texturally associated with barite: framboidal pyrite (py-I), which has negative δ 34 S values (−23‰ to −28‰; n = 9), and euhedral pyrite (py-II), which has markedly more positive δ 34 S values (+8‰ to +26‰; n = 86) . We argue that stratiform pyrite and barite developed along diagenetic redox fronts, where the isotopic relationships (δ 34 Spyrite ≈ δ 34 Sbarite ) are explained by anaerobic oxidation of methane coupled to sulphate reduction (AOM-SR). Furthermore, the relatively narrow distribution of δ 34 Sbarite values is consistent with an open system model of sulphate reduction, in which reduced sulphur generation occurred with a reduced isotopic fractionation (ε 34 S = <15‰) linked to higher rates of sulphate reduction and AOM-SR. Importantly, hydrothermal sulphides (pyrite, sphalerite and galena) all post-date this diagenetic barite-pyrite assemblage, and textural and mineralogical evidence indicates barite replacement to be an important process during hydrothermal mineralisation. Neither the textures nor the documented isotopic relationships can be produced by processes operating in a euxinic water column, which represents a major departure from the conventional model for SHMS formation at Macmillan Pass. We suggest that positive δ 34 S values in sulphides, a common feature of SHMS systems both in the Selwyn Basin and throughout the geologic record, could be linked to AOM-SR. At Macmillan Pass, positive δ 34 Spyrite values developed during open system diagenesis, which was critical for rapid sulphur cycling and the development of an effective metal trap.